Pertumbuhan Ekonomi: Pengaruh Pembiayaan dan Aset Tetap - Mariana, Mariana; Ramadana, Sri Winarsih; Rahmaniar, Rahmaniar (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2024)
This research aims to determine the effect of financing and total assets on economic growth. This research uses a quantitative approach with secondary data and applies multiple linear regression analysis methods. The population in this research are banks included in the LQ45 index from 2018 to 2022. The research results show that financing has an influence on economic growth. This shows that the decline in economic growth causes difficulties in purchasing or financing, prompting an increase in demand for bank financing. Conversely, high economic growth reduces the need for financing, resulting in reduced demand in the banking sector. Total assets have a significant influence on economic growth because the majority of total banking assets are used for internal banking purposes. This includes meeting capital needs, business expansion, improving service quality, and compliance with the principles governing banking operations, including sharia banking.